(untitled) (Revista Nacional de Odontología, 2017)
Introduction: The purpose of this research was to evaluate micromovements at the bone-implant interface using a provisional polyetheretherketone (peek) abutment and a polymethyl methacrylate (pmma) crown subjected to immediate loading, in order to establish whether these micromovements can impair implant osseointegration under normal loads. This evaluation was carried out through the finite element analysis (fem) method. Methods: A 13 mmL, 3.7 mmD Tapered Screw-Vent® implant (ref. (tsvb10 Zimmer Dental) was modeled with a 3.5 mm platform, a peek abutment, a screw, and a pmma crown of an upper central incisor. A cortical bone and a cancellous bone were modeled using Solid Works 2010 computer-aided design (cad) software (Solid Works Corp., Concord, Massachusetts, United States), and then processed and analyzed by the ansys 14.0 software. Micromovements at the bone-implant interface were evaluated by applying loads obliquely with a force of 200 Newtons on the palatal surface of the upper central incisor. Results: The cancellous and cortical bones showed micromovements with similar values (31.57 and 32.88 μm, respectively). Conclusions: The maximum micromovements occurred at the level of the implant neck. However, the high-density bone is prepared to receive implants with immediate loading without jeopardizing the osseointegration process.